Sunlight, vitamin D and food allergy. Issue 4 (August 2015) - Rudders, Susan A.; Camargo, Carlos A.
Abstract : Purpose of review: The role of vitamin D in the development of food allergy is unclear. We summarize recent data on the epidemiologic link between sunlight (UVB) and food allergy, and evidence for and against a specific role for vitamin D status. Recent findings: Since 2007, most epidemiologic studies have supported low sunlight (as measured by season of birth and latitude) as a risk factor for food allergy. Investigators have also looked directly at vitamin D status (as measured by serum 25OHD level) and its potential role. Although conflicting, the vitamin D studies suggest a more complicated association than a linear dose response in all individuals, with some studies indicating different associations based on host characteristics (e.g. concominant eczema, genetic polymorphisms, country of birth). Most studies have not fully examined the myriad effects of sunlight but have instead focused on a single maternal, neonatal or childhood 25OHD level. Summary: Many studies have linked sunlight with the development of food allergy but whether this is directly related to vitamin D status or a myriad of other sunlight-derived, seasonal and/or geographic factors remains uncertain. More studies are needed to investigate the role of sunlight and vitamin D status in food allergy because of their potential for primary prevention and disease modification.